(untitled) (Proceedings of the International Conference on Education, 2021)
COVID-19 is just the latest of a series of disruptions to the world’s economic order. Even before the pandemic, business models were being transformed by the demands of globalization, urbanization and disruptive technologies. As a consequence, almost every aspect of our lives is undergoing rapid change at an unprecedented pace. COVID-19 has modified not only the way we work, but also how workforces learn, collaborate and communicate. The pandemic has also seen a rapid movement to e-learning interventions, resulting in a rebalancing of power relationships between teacher and learner. However, an e-learning environment requires learners to take a more active role in their own learning, and as a result, as learners seek out greater active participation and engagement, they play a more significant role in the learning process (Seta et al., 2020). An outcome of this change is that within human capability programs in Indonesia, the ‘Teacher-centred’ style of presentation is losing cultural relevance, and there is a dynamic movement towards a more ‘Student-centred’ approach. The implications of this development are that trainers need to perform new, more non-traditional roles as mentors, coaches and learner guides (Fairman et al., 2020). To meet the requirements of these changes, there is a need to urgently reconsider the relevance of classical teaching approaches in Indonesia. This paper examines the learning and development programs as implemented by the National Institute of Public Administration (NIPA), which is largely responsible for building human resource capability across the Indonesian civil service (Murti, 2020). During the COVID pandemic, NIPA has moved from their ‘classical’ forms of training towards ‘online learning’, and the impact of this ‘shift’ has raised a number of challenges for NIPA staff and the role they play in developing Indonesia’s human capital.